SKIN DISEASES OF STREPTOCOCCAL ETIOLOGY IN INFANTS: ANALYSIS OF STREPTODERMA - Gulyamova Feruza (New modern researchers: modern proposals and solutions, 2025)
This article analyzes the causes, clinical symptoms, course and treatment of streptoderma in infants. Streptoderma is an acute infectious skin disease caused mainly by the bacterium Streptococcus pyogenes, which is widespread in infants due to the insufficient formation of the immune system. The study covers the clinical manifestations of streptoderma in infants, stages of diagnosis and effective treatment methods. It also provides scientific information on the complications of the disease and preventive measures.